Iraqi Constitution and European Constitution A Comparative Study of Citizenship - Hussein AL-Huseini, Mohammad Taha (International Journal of Psychosocial Rehabilitation, 2020)
Seventeen years after the US invasion, and following three rounds of elections, Iraq is one of the most unstable countries in the world. It is clear that the ill-conceived US experiment to remake Iraq has failed. The deep structural, legal, and political failings in trying to establish a stable legal-constitutional regime in a country that has suffered from a single, centralized, hierarchical government, it is not so easy even to understand the national population itself. And Iraq is now looking for a new future after the demise of dictatorial rule and is searching for democracy, freedom, and the rule of law. Therefore, this research aims to make a comparison between the Iraqi constitution and the European constitution, in order to reach recommendations that could contribute to amending the Iraqi constitution.